2019
DOI: 10.1016/j.kint.2019.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between galectin-3 and cystinosin uncovers a pathogenic role of inflammation in kidney involvement of cystinosis

Abstract: Interaction between galectin-3 and cystinosin uncovers a pathogenic role of inflammation in kidney involvement of cystinosis see commentary on page 275

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 51 publications
(64 reference statements)
4
22
0
Order By: Relevance
“…In addition, HSPCs isolated from the Rac2 −/− mouse model were enriched for a M(LPS/IFNγ) macrophage population but appeared to be as efficient in rescuing cystine build-up in the Ctns −/− mice as WT HSPCs. Our findings correlate with a recent study that demonstrated increased recruitment of proinflammatory immune cells in cystinosis, further highlighting the crucial role that inflammation plays in this disorder 49 . In addition, the dissonance between our in vitro and in vivo results reflects mounting evidence that the in vitro paradigm of macrophage activity can be a potentially misleading oversimplification 25 .…”
Section: Discussionsupporting
confidence: 91%
“…In addition, HSPCs isolated from the Rac2 −/− mouse model were enriched for a M(LPS/IFNγ) macrophage population but appeared to be as efficient in rescuing cystine build-up in the Ctns −/− mice as WT HSPCs. Our findings correlate with a recent study that demonstrated increased recruitment of proinflammatory immune cells in cystinosis, further highlighting the crucial role that inflammation plays in this disorder 49 . In addition, the dissonance between our in vitro and in vivo results reflects mounting evidence that the in vitro paradigm of macrophage activity can be a potentially misleading oversimplification 25 .…”
Section: Discussionsupporting
confidence: 91%
“…42 Lobry et al, demonstrated that cystinosin loss-of-function results in galectin-3 overexpression in cystinotic mice kidneys, inducing macrophage infiltration and kidney disease progression. 43 In light of our present data taken together with the clinical findings, we indicate that the V-ATPase B1 subunit plays an important role in acid-base homeostasis and is involved in the occurrence of a generalized proximal renal tubular defect that could functionally overlap with the one seen in cystinosis.…”
Section: Metabolic and Proteomic Profiling Link The Lysosomal V-atpassupporting
confidence: 59%
“…In this issue of Kidney International, the group of scientists led by Lobry et al 6 have discovered a new role for cystinosin function that adds to the understanding of why affected patients may have compromised kidney function as well. Using an established mouse model of the disease, the cystinosin knockout mouse (CTNS-/-), they demonstrated that in the normal mouse, cystinosin directed a protein galectin-3 to be degraded intralysosomally.…”
Section: See Basic Research On Page 350mentioning
confidence: 99%
“…The field eagerly awaits therapies directed at altering the many cellular processes that are disturbed, and now we can add one related to renal inflammation mediated by galectin-3 based on the work by Lobry and colleagues. 6 Additionally, we await innovative stem cell-based therapies that are now ongoing for a possible cure for nephropathic cystinosis. The future prospects for treating this disease have never been brighter, given the better understanding of the many cellular processes altered by a defective cystinosin.…”
Section: See Basic Research On Page 350mentioning
confidence: 99%